Insoles of uniform softer material reduced plantar pressure compared to dual-material insoles during regular and loaded gait - Melia, Georgia; Siegkas, Petros; Levick, Jodie; Apps, Charlotte (My University, 2020)
There is limited evidence on the efficacy of insole materials to reduce plantar pressure during regular walking and loaded walking. In-shoe plantar pressures and subjective footwear comfort were recorded in twenty healthy participants at a self-selected treadmill walking speed in six conditions: two commercial insoles or no insole, and with or without carrying a load in a backpack. A single-material insole, comprised of polyurethane, had reduced density and compressive stiffness compared to a dual-material insole with added viscoelastic material in rearfoot and forefoot regions. Load carriage increased peak pressure across the foot. Both insoles reduced plantar pressure in the rearfoot. Yet, the softer single-material insole also attenuated forefoot pressure and loaded walking did not appear to cause bottoming-out of the polyurethane. Plantar pressure changes did not affect perceived footwear comfort. The softer single-material insole was more effective in reducing plantar pressure, further research would confirm if this influences injury prevalence.
Keywords: Plantar pressure; Load-carriage; Density